2021
DOI: 10.3390/genes12081105
|View full text |Cite
|
Sign up to set email alerts
|

Embryo Screening for Polygenic Disease Risk: Recent Advances and Ethical Considerations

Abstract: Machine learning methods applied to large genomic datasets (such as those used in GWAS) have led to the creation of polygenic risk scores (PRSs) that can be used identify individuals who are at highly elevated risk for important disease conditions, such as coronary artery disease (CAD), diabetes, hypertension, breast cancer, and many more. PRSs have been validated in large population groups across multiple continents and are under evaluation for widespread clinical use in adult health. It has been shown that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…There is much enthusiasm for the use of PRS to inform individuals about their risk of future health conditions, either as stand-alone information, or combined with non-genetic data in integrated risk scores (Torkamani, Wineinger and Topol, 2018; Yanes et al ., 2020). PRS have been proposed in a wide variety of settings such as prioritizing people for disease screening, informing the prescription of preventive medicines, and even in embryo selection (Tellier et al ., 2021). Mutations in single genes associated with diseases are already utilised in a clinical setting, however, recent large-scale studies have found that PRS could potentially identify a greater proportion of at risk individuals (Khera et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is much enthusiasm for the use of PRS to inform individuals about their risk of future health conditions, either as stand-alone information, or combined with non-genetic data in integrated risk scores (Torkamani, Wineinger and Topol, 2018; Yanes et al ., 2020). PRS have been proposed in a wide variety of settings such as prioritizing people for disease screening, informing the prescription of preventive medicines, and even in embryo selection (Tellier et al ., 2021). Mutations in single genes associated with diseases are already utilised in a clinical setting, however, recent large-scale studies have found that PRS could potentially identify a greater proportion of at risk individuals (Khera et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This includes being accurately informed and counselled regarding scientific accuracy and utility of risk scores, absolute risk reduction and balancing risk scores for multiple conditions. [3][4][5]10,[53][54][55]61,62 A study in the United States concluded that at the moment genetic counsellors do not feel comfortable offering PGT-P, due to limitations of patient and provider education, research, accessibility and links to eugenics. 6 This indicates that informed decision-making regarding PGT-P is complex from both the provider's and the patient's side.…”
Section: Discussionmentioning
confidence: 99%
“…Common concerns relate, for example, to genetic determinism as well as the concepts of ancestry/ethnicity, where tools such as AI for risk stratification may not be representative of human diversity and whose development and use may distract attention from the social determinants of health ( Lewis and Vassos, 2020 ; Knoppers et al, 2021 ; Lewis and Green, 2021 ). Particular concerns about the risk of genetic discrimination and eugenics are raised with regard to the application of PRSs for embryo screening ( Treff et al, 2019 ; Tellier et al, 2021 ; Turley et al, 2021 ); most recently for pre-implantation genetic testing (PGT) ( Kozlov, 2022 ) and premature direct-to-consumer genetic testing/genetic counselling ( Docherty et al, 2021 ), which are also intertwined with marketability and commercialisation. Furthermore, due to underrepresentation of already underserved communities in the research process, some authors note that health disparities could increase through the use of PRSs in the clinical setting ( Martin et al, 2019a ).…”
Section: Ethical and Social Implications Of Prssmentioning
confidence: 99%